Avoiding the Target Language with the Help of Google: Managing Language Choices in Gathering Information for EFL Project Work. Issue 1 (15th May 2013) - Musk, Nigel
<x xml:space="preserve">Abstract</x> The integration of translation tools into the Google search engine has led to a huge increase in the visibility and accessibility of such tools, with potentially far‐reaching implications for the English language classroom. Although these translation tools are the focus of this study, using them is in fact only one way in which English language learners can exercise their language preferences, especially when working more autonomously. By acting upon these preferences and opting to read in their first language, learners effectively adopt an avoidance strategy—that of avoiding the target language. This qualitative study highlights several ways in which pupils can and do exercise their language choices in their computer‐assisted project work using (Swedish) Google. More specifically, after mapping out the trajectories of pupils' Internet searches and their gathering of resources, conversation analysis is used to zoom in on key moves that are jointly negotiated at the interface with Google, where different language options are made available and even flagged. By making incremental choices that avoid English (or favour Swedish), the visibility of English can diminish radically, if not altogether. The negative implications of avoidance are discussed as well as the practicalities of solutions using Google itself.